SISTEM INFORMASI GEOGRAFIS DALAM PENETAPAN PAJAK BUMI DAN BANGUNAN - Muliantara, Agus (Jurnal Ilmu Komputer; Vol. 2, No. 1 April 2009)
Tax is a country’s asset that is very important. With the tax the development can be heald. One of the tax that is land and building tax. Land and building tax is a tax charged to the person who has the tax object.. Determining the amount of tax payable by a compulsory tax, varies depending on the type of land use, area and the selling price. Geographical Information System mapping systems have the accuracy, expected later determination process and the monitoring of the land and building tax can be more optimized for that, this research carried out on the determination and monitoring of land and building tax using Geographical Information System.In the implementation, this research will use the Microsoft .Net framework. And MapX as a mapping tool that will be used in the management of data objects, including tax map editing. And using IIS as web server and mapXtreem as a map server that functions as a provider of information objects to the tax assessable on the internet.Determination of tax trials conducted in comparison with the original data in year 2000, 2001 for the village pentaih kecamata Denpasar Bali Barat province with the goal to make assasment whether the system is able to provide the same tax rate. And the results of the pilot is the software that can run well enough. Which is able to set the amount of tax and land and buildings capable of carrying out monitoring of the tax Penatih village.
Keywords: Tax Object, assessable, determining and monitoring